Farm Forestry - Phillips, George R. (Indian Forester, 1946)
This paper presented at a meeting of the washington Section, Society of American Foresters, on January 23, 1945, stresses the importance of better management of the country’s 185 million acres of farm woodland. From the standpoint of each of the 31/2million farmers involved, such management is intinately connected with proper management of his entire farm- the production plant from which he earns his living. Full use needs to be made of public and private educational service and facilities to help instill into the cultural pattern of our farmers an inherent desire to operate their farms so that their woodlands are properly managed.